A compreensão da identidade do leigo nos documentos das conferências gerais do Celam - Gomes, Dorcelina do Carmo Alves (2020)
The main objective of this Dissertation is to propose a theological reflection on the understanding of the identity of the lay faithful Christian in the final documents of the General Conferences of the Latin American and Caribbean Episcopal Council (CELAM), held after the Second Vatican Ecumenical Council (1962 1965) :Medellín (1968), Puebla (1979), Santo Domingo (1992) and Aparecida (2007). The research starts from the study of the presentation of the identity of the lay faithful at the Second Vatican Ecumenical Council, especially in chapter IV of the Dogmatic Constit ution Lumen Gentium and in the Apostolic Decree Apostolicam Actuositatem , more in the post synodal Ap ostolic Exhortation Christifideles Laici , of Pope John Paul II, because they became the basis for the o logical and pastoral reflection on the faithful lay Christian in the General Conferences of the episcopate of Latin America and the Caribbean. Considering the historical and the o logical contextualization of the conciliar text and the subsequent reception, the research presents the thinking about the lay person in the four General Conferences, to finally conclude with a synthesis of the ological and pastoral thinking extracted from the analysis of the final texts of the Conferences. The dissertation defends that the layman's identity is, necessarily, its secular nature, which is peculiar to him.